Synthesis and Luminescence Properties of the Binary/Ternary Complex of Samarium Ion with Phenacylmethyl P-Tolyl Sulfoxide and Benzoic Acid - Yang Kui-Suo; Li Wen-Xian; Bao Jin-Rong (MATEC Web of Conferences, 2018)
A new ligand phenacylmethyl p-tolyl sulfoxide (denoted as L1) has been synthesized by an asymmetric synthesis method. Its novel binary complex Sm(L1)7·(ClO4)3·6H2O, and ternary complex Sm(L1)6·(L2)·(ClO4)2·6H2O (benzoic acid denoted as L2) have been synthesized. The structure and composition of the samarium complexes characterized by elemental analysis, molar conductivity, IR, UV, and 1HNMR. Additionally, fluorescence spectra measurements shows that the complexes display stronger fluorescence intensity in solid state, indicating the ligands could efficiently transfer the energy to Sm3+ ions in the complexes. The ternary complex has stronger fluorescence intensity than the binary complex.